MENGEMBANGKAN BUDAYA ISLAM BERKEMAJUAN MELALUI LEMBAGA PENDIDIKAN - Azizah, Azizah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2024)
The purpose of this research is to conduct an empirical and practical study of the characteristics of progressive Islam and inculturation in Muhammadiyah educational institutions. In turn, it will be an inspiration and model of progressive education in the world of education. The research method is to use literature sources (library research). This means that the data and study materials used are from library sources. As for the results of the study that the characteristics of progressive Islam (al-Islam al-Taqaddumi), which includes a progressive view of Islam in five characteristics (al-Khasha'ishu alhamsu). These characteristics are: (1) Based on Tawhid (al-Mabni 'ala al-Tauhid); (2) Emphasising human thought from shirk, syncretism and religious nationalism; (3) Upholding reason and science; (4) Promoting social justice; (5) Emphasising the importance of noble character. The inculturation of progressive education is done by First, building schools that integrate religious and general education and strengthen school branding. Second, developing education based on social life and the needs of society and the world of work. Third, reforming the system and values by adopting modern values of the 21st century.